2015
DOI: 10.1002/lary.25716
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease and odds of head and neck squamous cell carcinoma in North Carolina

Abstract: 3b. Laryngoscope, 126:1091-1096, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…The relationship between GERD and non‐oropharyngeal HNSCC is mixed with many earlier studies suggesting an association with hypopharynx or larynx cancer, but recent studies have not supported these findings 23‐26 . Our study is the first study of PLWH to examine GERD, in which we observed an association of GERD with non‐oropharyngeal HNSCC.…”
Section: Discussioncontrasting
confidence: 66%
“…The relationship between GERD and non‐oropharyngeal HNSCC is mixed with many earlier studies suggesting an association with hypopharynx or larynx cancer, but recent studies have not supported these findings 23‐26 . Our study is the first study of PLWH to examine GERD, in which we observed an association of GERD with non‐oropharyngeal HNSCC.…”
Section: Discussioncontrasting
confidence: 66%
“…Several previous studies have tested for the association between GERD and laryngeal squamous cell carcinoma (LSCC), but the results have been inconsistent 6‐13 . Most previous studies have been limited by size, study design, or insufficient control for important potential confounders (eg, tobacco use and alcohol consumption 14‐16 ), limiting the strength of the inference 17‐19 .…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have tested for the association between GERD and laryngeal squamous cell carcinoma (LSCC), but the results have been inconsistent. [6][7][8][9][10][11][12][13] Most previous studies have been limited by size, study design, or insufficient control for important potential confounders (eg, tobacco use and alcohol consumption [14][15][16] ), limiting the strength of the inference. [17][18][19] A recent meta-analysis summarizing 15 case-control studies revealed a 2.37-fold higher risk of LSCC among individuals who have GERD, 13 while other studies have suggested that this association is driven largely by residual confounding due to unmeasured variables such as tobacco use and alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that non-acidic reflux promotes the development of laryngeal carcinoma. [22][23][24] Thus, the relationship between LPRD and laryngeal carcinoma requires further investigation.…”
Section: Introductionmentioning
confidence: 99%